REDUCTION OF INTRA-ARTICULAR ADHESION BY TOPICAL APPLICATION OF DAIDZEIN FOLLOWING KNEE SURGERY IN RABBITS - Liu, Xiangchun; Jia, Heng; Xia, Hongsheng (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Intra-articular adhesion is the commonest complication that is faced by orthopedic surgeons after knee surgery. Thus, the present investigation evaluates the effect of daidzein on intra-articular adhesion in rabbits. Material and methods: All the rabbits were separated in to four different groups each group carries ten rabbits. Cancellous bone was exposed in each rabbit by removing cortical bone from both side of the femoral condyle. Following daidzein (2.5, 5 and 10 mg/ml) was topically applied for the duration of 10 min to the decorticated areas. Thereafter for the period of 4 week surgical limb was fixed. Effect of daidzein on intra articular adhesion was estimated by visual score through macroscopic examination, histopathology study, hydroxyproline content, fibroblast and collage density. Results: Data obtained in the study suggest that topical application of daidzein (5 and 10 mg/ml) loose the collagen and significantly decreases the adhesion at the decorticated areas. Moreover there were significant reduction in the fibroblast density, hydroxyproline content and optical density of collagen tissue in daidzein (5 and 10 mg/ml) treated group than control. Conclusion: Thus present study concludes that topical application of daidzein reduces intra-articular adhesion around the knee.